LEGAL VALUES AND MORALS IN ECOLOGICAL PRACTICES OF SANTUBONG COMMUNITY - Awaluddin, Syah; Bin Ali , Mohamad Fairuz (Journal Of Law And Social Society, 2025)
This study explores the integration of legal values and morality in the ecological practices of the Santubong community, Sarawak, Malaysia. The Santubong community, comprising diverse ethnic groups such as Malay, Iban, Bidayuh, and Chinese, demonstrates a high level of ecological awareness through the integration of traditional wisdom, legal frameworks, and moral principles. This research employs a qualitative approach with a case study method, using Focus Group Discussions (FGD), participant observation, and document analysis to collect data. The findings reveal that the Santubong community applies ecological justice, sustainability, responsibility, and respect for nature through customary laws and everyday practices. Their legal values are reflected in sustainable forest management, water conservation, waste management, and biodiversity protection. Meanwhile, moral principles such as respect for nature, collective responsibility, and ethical behavior drive community participation in environmental conservation. The synergy between legal and moral frameworks contributes to effective ecological governance, ensuring that conservation efforts are not only legally compliant but also socially accepted and morally guided. This study concludes that the Santubong community offers a valuable model of ecological governance, demonstrating that the integration of law and morality can support sustainable environmental management and provide insights for broader ecological policies.